The Effect of Kelong-Oriented Contextual Approach on the Cognitive Science Learning Outcomes - Wahyuni, Rizka; Zulirfan, Z.; Maaruf, Zuhdi (Journal of Indonesian Science Teachers, 2024)
This research aims to improve students' cognitive learning outcomes by using a contextual approach oriented towards traditional kelong fishing gear. This research method uses a quasi-experiment with a non-equivalent post-test only group design. The population in this study was class VIII students, totaling 79 people. The population came from three classes, of which 2 classes were then selected for the research sample, namely class VIII-1 as the experimental group and class VIII-2 as the control group. The research was carried out in four meetings. After learning is complete, students are given a posttest in the form of a cognitive learning outcomes test instrument with 25 multiple-choice questions. The average score data on student learning outcomes shows differences between the experimental class and the control class. The experimental class obtained an average score of 72.90 in the good category, while the control class obtained an average score of 59.37 in the quite good category. Then, based on the independent sample T-Test, the significance results were 0.000 < 0.05. Therefore, learning with a contextual approach oriented towards traditional kelong fishing gear is effectively used to improve cognitive science learning outcomes for students at SMPN 1 Lingga Utara.